IMPACT OF THE FREQUENCY OF USING NONSTEROIDAL ANTI-INFLAMMATORY DRUGS ON THE RADIOGRAPHIC PROGRESSION OF SACROILIITIS IN PATIENTS WITH EARLY AXIAL SPONDYLOARTHRITIS - D. G. Rumyantseva; T. V. Dubinina; Sh. F. Erdes (Научно-практическая ревматология, 2018)
Objective: to compare the impact of continuous or on-demand use of nonsteroidal anti-inflammatory drugs (NSAIDs) on the activity and radiographic progression of early axial spondyloarthritis (axSpA).Subjects and methods. The investigation enrolled patients from the early spondyloarthritis cohort who met the 2009 Assessment of Spondyloarthritis International Society (ASAS) criteria for axSpA. This analysis included 68 patients who had been followed up for at least 24 months. The mean age at the time of inclusion in the investigation was 28.5±5.8 years; the mean disease duration was 24.1±15.4 months; 63 (92.6%) patients were HLA-B27-positive. The patients were divided into two groups: 1) 35 patients used NSAIDs at maximum therapeutic doses continuously during the follow-up period; 2) 33 patients received these drugs on-demand, depending on the presence and severity of back pain.Results and discussion. After 2-year follow-up, the median stage of radiographic sacroiliitis (SI) in Group 1 was unchanged and remained equal to 4; that in Group 2 in this period significantly increased from 3 to 4 scores (p < 0.05). At baseline, the patient groups did not differ in C-reactive protein (CRP) levels, the Ankylosing Spondylitis Disease Activity Score (ASDAS-CRP), and the Bath Ankylosing Spondylitis Functional Index (BASFI); however, the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) was higher in Group 1 (p < 0.05). The number of patients with active SI, as evidenced by magnetic resonance imaging (MRI), and the degree of its severity did not differ significantly between groups. After 2 years, all the patients retained low disease activity according to ASDAS-CRP, BASDAI, and CRP levels; and these measures did not differ significantly between groups either; the BASFI became higher in Group 1. MRI findings indicated that the number of patients with active SI decreased, but no differences were found between the groups.Conclusion. In patients with early axSpA, the continuous intake of NSAIDs can slow radiographic progression to a greater extent than their on-demand use.